Non-Destructive Testing of Structures - Rucka, Magdalena (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The Special Issue "Non-Destructive Testing of Structures" has been proposed to present the recent developments in the field of the diagnostics of structural materials and components in civil and mechanical engineering. The papers highlighted in this editorial concern various aspects of non-invasive diagnostics, including such topics as the condition assessments of civil and mechanical structures and the connections of structural elements, the inspection of cultural heritage monuments, the testing of structural materials, structural health monitoring systems, the integration of non-destructive testing methods, advanced signal processing for the non-destructive testing of structures (NDT), damage detection and damage imaging, as well as modeling and numerical analyses for supporting structural health monitoring (SHM) systems.